Case Report: Atypical visual presentation caused by a large convexity meningioma—a nerve stretching and stalk indentation effect - Chiu, Chia-Hsun; Chen, Ko-Ting (Frontiers in Surgery, 2024)
Visual field defects commonly present in patients with brain tumors particularly due to direct compression on the optic apparatus. However, there are instances where brain tumors, despite not directly compressing the optic pathway, can still cause visual symptoms, albeit rarely reported but not uncommonly observed. These mechanisms are thought to be associated with increased intracranial pressure (IICP).We report a case of a 32-year-old man presented with right blurred vision and was diagnosed with right convexity meningioma. Upon reviewing his magnetic resonance images, we hypothesized the indentation of the pituitary stalk on the optic chiasm and the stretching of the optic nerve, combined with a focal effect of IICP, could be responsible for his atypical visual field defect.